Restriction of the rotational relaxation of a butadiyne-bridged porphyrin dimer in ultrathin films. (3rd July 2019) - Shokurov, Alexander V.; Meshkov, Ivan N.; Bulach, Véronique; Gorbunova, Yulia G.; Hosseini, Mir Wais; Tsivadze, Aslan Yu.; Arslanov, Vladimir V.; Selektor, Sofia L.
Abstract : A way to stabilize the less energetically viable orthogonal conformation of a porphyrin dimer by means of a forced orientation at an interface is shown. Abstract : The dynamic behaviour of a porphyrin dimer, based on the covalent linkage of two macrocyclic moieties with a butadiyne connector, was studied in thin films by UV-Vis and emission spectroscopies. The degree of π-conjugation through control of intramolecular motion was investigated without employing extreme conditions such as cryogenic temperatures or high viscosity. By exploiting the propensity of the dimer to bind axial ligands through Zn–N bonds, it was shown that the co-planar and orthogonal conformations of the dimer may be stabilized in ultrathin films at the air/water interface. Furthermore, using the Langmuir–Blodgett technique, monolayer-thick matrix-free films on solid substrates containing the porphyrin dimer were obtained. In the latter case, the dimer exists in either an exclusively co-planar state or a mixture of conformational states depending on the nature of the axial ligand: 1, 4-diazabicyclo[2.2.2]-octane (DABCO) or 4-aminomethylpyridine (AMP).